2017
DOI: 10.1016/j.engstruct.2016.09.057
|View full text |Cite
|
Sign up to set email alerts
|

Experiments and simulations of empty and sand-filled aluminum alloy panels subjected to ballistic impact

Abstract: In this study, we use a discrete particle method in combination with finite element analysis to describe the interaction between structures and granular media during ballistic impact. By applying a discrete particle method to model granular materials, issues like mesh distortion and element deletion can be avoided. This paper presents experiments and numerical simulations on the perforation of empty and sand-filled aluminum alloy panels subjected to impacts by small-arms bullets. The simulations of the sand-fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…As one of the most complicated struggles in solid mechanics, high-velocity impact has been-and will remain-a major topic of interest among many researchers specially in aerospace field [1][2][3][4][5][6][7]. In this respect, researchers have to fully comprehend and aptly analyze the process of projectile penetration in designing structures.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most complicated struggles in solid mechanics, high-velocity impact has been-and will remain-a major topic of interest among many researchers specially in aerospace field [1][2][3][4][5][6][7]. In this respect, researchers have to fully comprehend and aptly analyze the process of projectile penetration in designing structures.…”
Section: Introductionmentioning
confidence: 99%
“…Structures made of aluminium alloys are widely applied in the construction industry [ 1 , 2 , 3 ], the aerospace and aviation industry [ 4 , 5 ], the automotive industry [ 6 , 7 ] and military applications [ 8 ]. The popularity of this material is mainly due to its relatively low density, good strength-to-mass ratio, high corrosion resistance, and good ability to be welded, including with other materials [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the corresponding study by Holmen et al [27] perforation of empty and sand-filled aluminium panels was investigated. It was shown that though the combination of the finite element analysis (Johnson-Cook plasticity and failure models) and the discrete particle method can be used to describe interaction between solid and granular media, still some challenges remain.…”
Section: Introductionmentioning
confidence: 99%